PENTINGNYA PELAYANAN BIMBINGAN DAN KONSELING DI PENDIDIKAN TINGGI; PERSPEKTIF MAHASISWA PENDIDIKAN BIOLOGI - Rahmawati Darussyamsu; Neviyarni Suhaili; Mudjiran Mudjiran; Herman Nirwana (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to reveal the importance of guidance and counseling services in higher education based on the views of biology education students. The research was conducted using in-depth interview techniques on three students with high, medium, and low abilities. Considering the health protocol during the Covid-19 pandemic, the interview was conducted by telephone. Research findings reveal that students are not aware of the existence of guidance and counseling services in universities. Knowledge about guidance and counseling that students have is derived from experience in senior high school and also from guidance and counseling lecture material which generally discusses guidance and counseling at school. All informants have a good perception of guidance and counseling services. In addition, informants agreed that students really need guidance and counseling service programs on campus, because various student problems cannot always be solved by telling stories to friends or academic advisors. Based on the fact that informants did not know about counseling services, the informants suggested that better socialization be given to students about the existence of counseling services in universities, so that they could effectively overcome various problems faced by students.